أنماط صورة الصحراء في ديوان "من أغاني الطاسيلي" لمبروك بالنوي - بريم, صباح (جامعة الوادي - university of Eloued, 2021)
صورة الصحراء واحدة من الصور المهيمنة على أغلب قصائد شعراء الجنوب الجزائري، فهي تجمع بين البيئة التي احتضنتهم وكبروا هم فيها وكبُرت هي فيهم، وبين كونها جزء من هويتهم وأصالتهم. ولهذا كان لها حضورا مميزا لديهم. وديوان "من أغاني الطاسيلي" للشاعر مبروك بالنوي واحد من الدواوين التي برزت فيها صورة الصحراء، وتغلغلت في كل ثناياه. ومن أجل الاطلاع أكثر على صورة الصحراء في هذا الديوان؛ بنينا بحثنا هذا للإجابة على التساؤل الآتي: ما الأنماط التي جاءت عليها هذه الصور؟ Abstract : The image of the desert is one of the dominant images in most of the poems of southern Algerian poets. It combines the environment in which they were embraced and grown up in, and is part of their identity and originality. That is why she had a distinguished presence with them. And the diwan "From the Tassili Songs" by the poet Mabrouk Balnawi is one of the diwans in which the image of the desert emerged and permeated all its folds. For more information on the desert image in this diwan; We endeavoured this research to answer the following question: What patterns did these images have?
مقال
Keywords: الصورة الشعرية؛ الصحراء؛ شعراء الصحراء؛ أنماط الصورة، مبروك بالنوي; poetic pictures. Desert. Poets of the Desert. Image patterns. Mabrouk Benaoui